Biomonitoring of Nicotine Exposure in Tobacco Farmers with Green Tobacco Sickness Symptoms - Yunita Fristiyanwati; Muhammad Ilyas (The Indonesian Journal of Occupational Safety and Health, 2022)
Introduction: Indonesia is the fifth tobacco producing country in the world. The climate and weather in Indonesia are very suitable for tobacco plantations. At harvest season, tobacco farmers face the risk of being exposed to nicotine compounds due to skin contact with tobacco leaves. This exposure can cause a syndrome known as Green Tobacco Sickness (GTS) with symptoms of nausea, vomiting, weakness, dizziness, headache, insomnia and loss of appetite. These symptoms are not specific enough to describe GTS, so biological monitoring is required. As one of the main metabolites, cotinine has been used as a biological marker to assess nicotine exposure. This study aims to examine the reliability of nicotine biomonitoring in tobacco farmers with symptoms of GTS. Methods: We searched the online electronic databases, namely PubMed, Cochrane, and Scopus for appropriate evidence based material. We then made adjustments using the inclusion and exclusion critertia to then conduct a critical review of the selected articles. Results: We obtained four articles, consisting of 3 articles examining urinary cotinine as a biomarker of nicotine exposure, and another 1 article examining cotinine saliva. The articles gave us the similar pattern that in tobacco farmers with GTS symptoms there was an increase in cotinine levels, both measured in urine and saliva. Conclusion: Based on the articles obtained, cotinine, as a nicotine metabolite, can be a reliable biomarker assessing nicotine exposure in tobacco farmers with GTS symptoms. However, more research is needed to compare the best selection of biological samples such as urine, blood or saliva.